Global E × B flow pattern formation and saturation. (1st December 2022) - Qi, Lei; Choi, M.J.; Leconte, M.; Hahm, T.S.; Kwon, Jae-Min
Abstract: The E × B flow staircase-like pattern observed in the first principle gyrokinetic numerical experiments of tokamak fusion plasmas forms due to a nonlinear time delay. Simulations demonstrate a finite time delay between the staircase occurrence in particle transport and that in the density profile. This novel finding shows that instability can arise from perturbations in transport and then influence the background turbulence. E × B flow staircase plays roles not only in shearing the transport but also as a nonlinear saturation mechanism of staircase instability. Experimental measurements in KSTAR tokamak L-mode plasmas are consistent with the numerical findings.